Analisis Kinerja Turbin Angin Sumbu Vertikal Tipe H-Darrieus Dengan Sudu Naca 0015 Menggunakan Pendekatan Computational Fluid Dynamic (CFD) - Pranasmara, Nicolas Yoga (Journal of New Energies and Manufacturing, 2023)
Wind energy as renewable energy has the potential to be developed. In Urban Area with the characteristics of unstable airflow patterns and relatively low environmental impact, the Vertical Axis Wind Turbine (TASV) becomes a potential power plant to convert wind kinetic energy into electrical energy. This study aims to the performance of the straight bladed H-Darrieus TASV with variation of blade configurations (2 and 3) and wind speed (1,3,5,8, and 10 m/s). The shape of the blade used the NACA 0015 airfoil. The method used in this research is a two-dimensional numerical study using Computational Fluid Dynamic (CFD) with the tip speed ratio at 1.31. The results showed that the maximum power coefficient (Cp) of 0.02 occurred at a wind speed of 8 m/s with a configuration of 2 (two) blades. At wind speeds of 1, 3, 5, and 10 m/s, the configuration of 3 (three) blades has a higher Cp value than the configuration of 2 (two) blades. But the configuration of 2 blades has higher Cp value than the 3 (three) blade configuration at a wind speed of 8 m/s